Green magnesium oxide nanoparticles-based modulation of cellular oxidative repair mechanisms to reduce arsenic uptake and translocation in rice (Oryza sativa L.) plants. (1st November 2021) - Ahmed, Temoor; Noman, Muhammad; Manzoor, Natasha; Shahid, Muhammad; Hussaini, Khalid Mahmud; Rizwan, Muhammad; Ali, Shafaqat; Maqsood, Awais; Li, Bin
Abstract: Arsenic (As) accumulation catastrophically disturbs the stability of agricultural systems and human health. Rice easily accumulates a high amount of As from agriculture fields as compare with other cereal crops. Hence, innovative soil remediation methods are needed to deal with the detrimental effects of As on human health causing food security challenges. Here, we report the green synthesis and characterization of magnesium oxide nanoparticles (MgO-NPs) from a native Enterobacter sp. strain RTN2, which was genetically identified through 16S rRNA gene sequence analysis. The biosynthesis of MgO-NPs in reaction mixture was confirmed by UV–vis spectral analysis. X-ray diffraction (XRD) and fourier transform-infrared spectroscopy (FTIR) analysis showed the crystalline nature and surface properties of MgO-NPs, respectively. Moreover, electron microscopy (SEM-EDS, and TEM) imaging confirmed the synthesis of spherical shape of MgO-NPs with variable NPs sizes ranging from 38 to 57 nm. The results revealed that application of MgO-NPs (200 mg kg −1 ) in As contaminated soil significantly increased the plant biomass, antioxidant enzymatic contents, and decreased reactive oxygen species and acropetal As translocation as compared with control treatment. The study concluded that biogenic MgO-NPs could be used to formulate a potent nanofertilizer for sustainable rice production in metal contaminated soils. Graphical abstract: Image 1 Highlights: Biogenic MgO-NPs were synthesized by using a native bacterium Enterobacter sp. RTN2. Characterization of biogenic MgO-NPs by spectroscopic and microscopic techniques. MgO-NPs promoted the morpho-physiological profiles of arsenic stressed rice plants. MgO-NPs decreased the ROS and inhibited arsenic translocation in rice plants.